Near-unity NIR phosphorescent quantum yield from a room-temperature solvated metal nanocluster - Shi, Wan-Qi; Zeng, Linlin; He, Rui-Lin; Han, Xu-Shuang; Guan, Zong-Jie; Zhou, Meng; Wang, Quan-Ming (Science (American Association for the Advancement of Science), 2024)
Metal nanoclusters have emerged as promising near-infrared (NIR)–emissive materials, but their room-temperature photoluminescence quantum yield (PLQY), especially in solution, is often low (<10%). We studied the photophysics of Au 22 ( t BuPhC≡C) 18 (Au 22 ) and its alloy counterpart Au 16 Cu 6 ( t BuPhC≡C) 18 (Au 16 Cu 6 ) (where t Bu is tert -butyl and Ph is phenyl) and found that copper (Cu) doping suppressed the nonradiative decay (~60-fold less) and promoted intersystem crossing rate (~300-fold higher). The Au 16 Cu 6 nanocluster exhibited >99% PLQY in deaerated solution at room temperature with an emission maximum at 720 nanometers tailing to 950 nanometers and 61% PLQY in the oxygen-saturated solution. The approach to achieve near-unity PLQY could enable the development of highly emissive metal cluster materials. Gold nanoclusters have potential applications as near-infrared emissive materials for biological applications but often exhibit low photoluminescence quantum yield (PLQY) in solution at room temperature. Shi et al . found that copper substitution to form an Au16Cu6 cluster improved the PLQY to more than 60% in oxygenated solutions at room temperature. The presence of copper led to ultrafast intersystem crossing to the long-lived triplet state and also suppressed nonradiative decay. —Phil Szuromi A copper-doped gold cluster exhibited ultrafast intersystem crossing and suppressed nonradiative decay after photoexcitation.